Metals in mine wastes: environmental pollution and soil remediation approaches – a review. Issue 3 (4th May 2021) - El Rasafi, Taoufik; Nouri, Mohamed; Haddioui, Abdelmajid
Abstract: Millions of hectares in Africa, Europe, Asia, Australia, and America are contaminated of mine wastes. This contamination has caused a serious danger to humans, animals, plants, and microorganisms near mine sites. Such contamination may cause kidney dysfunction, reproductive deficiencies, mental retardation, or even death. These sites need to be remediated urgently to minimize their effect and for safety of the ecosystem and the environment health. Different approaches were used including chemical, physical, and biological approaches. Due to the limitations of the physicochemical techniques, the major interest was been devoted to the biological techniques, especially the phytoremediation. These techniques are considered as the future solution for cleaning the contaminated sites with mine wastes. The present review discusses the metals in mine wastes and their effects of humans, animals, plants, and microorganisms as well as the used remediation techniques to treat the contaminated soils.